Haemangiosarcoma of the Eyelid in a Four-Year Old Balami Ram - Abubakar Sauidu; Mohammed Umar; Halima Gambo; Shehu Hassan; Wiam Manhzhia; Abdullahi Mohammed (Iranian Journal of Veterinary Surgery, 2013)
Case Description-A four-year old Balami ram weighing 120kg was presented to the University of Maiduguri Veterinary Teaching Hospital (UMVTH) with extensive swelling and ulceration of the nictating membrane of the left eye. Clinical Findings-A dark red hard mass on the third eyelid was covering the entire eyeball. The visible mass measured 5cm vertically and 7cm horizontally. Pus exudate was expressed from the nictating membrane. Full blood count revealed normal blood values. Treatment and Outcome-Treatment involved surgical removal of the hard mass by thermocautery under sedation and general anaesthesia. The ram was premedicated with Xylazine hydrochloride 0.1mg/kg IV. General anaesthesia was induced and maintained with Ketamine hydrochloride 5mg/kg IV. Histopathological examination of samples showed numerous vascular spaces lined by multilayered neoplastic endothelia. Complete surgical excision was not curative due to recurrence. Clinical Relevance- Haemangiosarcoma are common tumors in dogs, cats, horses and swine and only few cases in ovine species were reported for the first time in the last decade. Eyelid tumours cause discomfort, interfere with eyelid function and may cause keratitis and Surgery remains the basic method of treatment in oncology.